Ingested Walnut Oil Can Prevent Low-Fat/High-Carbohydrate diet and High-Fat Diet-Induced Obesity by Modulating Metabolic Health Markers and Regulating the Expression of Genes for Metabolism - Juturu, Vijaya; Şahin, Kazım; Orhan, Cemal; Tuzcu, Mehmet; Şahin, Nurhan (Wiley, 2017)
[Abstract Not Available]
Experimental Biology (EB) Annual Meeting -- APR 22-26, 2017 -- Chicago, IL